Effect of Citronella Aromatherapy on Appetite and Sleep Quality in Stunted Toddlers: A Community-Based Intervention Study - Irdasari, Yuli; Risnawati; Hartati, Dwi; Sumiati, Hj (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Stunting is a major global health issue linked to chronic malnutrition, digestive dysfunction, and inadequate sleep, all of which impair growth and nutrient absorption. Toddlers with poor sleep quality are twice as likely to experience stunting, highlighting the importance of behavioral and sensory interventions. Citronella Oil aromatherapy, containing active compounds such as citronellal and geraniol, has potential appetite-enhancing and relaxing effects through olfactory stimulation of ghrelin and the limbic system. This study aimed to evaluate the effect of Citronella Oil aromatherapy on appetite and sleep quality among stunted toddlers aged 2–3 years in the working area of UPTD Tepian Buah Health Center, Berau Regency. A pre-experimental one-group pretest–posttest design was applied, involving 55 participants selected through stratified random sampling. Appetite and sleep quality were measured using validated questionnaires, and data were analyzed using the Wilcoxon signed-rank test. Results showed a significant increase in mean appetite scores (from 37.40 to 44.76) and sleep quality scores (from 7.24 to 12.82) after seven days of Citronella Oil aromatherapy (p<0.05). These findings indicate that Citronella Oil effectively improves both appetite and sleep quality in stunted toddlers through neuroendocrine and behavioral mechanisms. The intervention offers a safe, low-cost, and culturally appropriate complementary therapy that may strengthen early childhood growth and development programs. However, limitations include a small sample size, the absence of a control group, and a short intervention duration, which constrain generalizability. Future studies using randomized controlled and longitudinal designs are recommended to confirm these findings. Beyond its local implications, this research contributes to global efforts to identify sustainable, non-pharmacological strategies to reduce stunting and advance holistic child health in low- and middle-income countries.